“You Know What I’m Saying”: Emic and Etic Considerations in Research Involving Sexual Minorities - Thomas V. Bettinger (Adult Education Research Conference, 2008)
This paper focuses on the implications of being an “insider” (emic perspective) versus being an “outsider” (etic perspective) when conducting research involving sexual minorities.
Keywords: sexual minorities; emic; etic; insider; outsider